Basal cell carcinoma: the utility of in vivo and ex vivo confocal microscopy. (18th May 2018) - Longo, C.; Borsari, S.; Pampena, R.; Benati, E.; Bombonato, C.; Raucci, M.; Mirra, M.; Di Stefani, A.; Peris, K.; Pellacani, G.
Abstract: The use of confocal microscopy is possible using two different modalities: first, at patient's bedside for a rapid in vivo diagnosis of basal cell carcinoma and second, in the operating room directly on freshly excised specimen for a fast ex vivo margin‐controlled surgery. In the current review, we report the main application of confocal microscopy for basal cell carcinoma diagnosis and management in both modalities.